answersLogoWhite
notificationBell

Top Answer
User Avatar
Wiki User
Answered 2014-05-12 21:03:01

6 minus 3 and two thirds = 2 and one third.

001
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
๐Ÿ˜‚
0
User Avatar

Your Answer

Related Questions


Two thirds minus two ninths is 4 ninths. Two thirds is 6 ninths. 6 ninths minus 2 ninths is 4 ninths.


6 2/3 - 1 =5 2/3 the answer five and two thirds.



It is: 2/3 minus 7/6 = -1/2


2/3 minus 1/6 is the same as 4/6 minus 1/6 = 3/6 or 1/2 simplified


9 - 11 - 2 - 2 2/3 + 6 1/3 = -1/3 or minus one third. Expressed as a decimal, this is equal to -0.3 recurring (that is, -0.3333...)



5(1/6) - 2(2/3) = 31/6 - 8/3 = 31/6 - 16/6 = 15/6




4 and two thirds = (4(3)+2)/3 = 14/3 6 times 4 and two thirds = 6 * (14/3) = 28


3 there are 6 thirds total, in 2. If you group the thirds in groups of 2 then you will have 3 groups or 6 thirds divided by 2 = 3


31/2 - 2/3 = 7/2 - 2/3 = 21/6 - 4/6 = 17/6 = 25/6


Two Thirds is 2/3. So, 2/3 equals: 4/6, 6/9..........


2/3 can be converted to 4/6. So 4/6 - 1/6= 3/6 or 1/2


It is: 1/6 minus 2/3 = -1/2


72/3 - 45/6 = 23/3 - 29/6 = 46/6 - 29/6 = 17/6 = 25/6


2/3 is equivalent to 4/6 4/6-1/6= 3/6 (in simplest form 1/2)


5/6 - (-2/3) = 5/6 + 2/3 = 5/6 + 4/6 = 9/6 = 1 1/2



6, one third is 3 so two thirds is 6


(5-1/2) - (2/3) = (11/2) - (2/3) = (33/6) - (4/6) = (29/6) = 4-5/6


3 2/3 - 1 1/2=11/3 - 3/2= 22/6 - 9/6 = 13/6= 2 1/6



Expressed as a vulgar fraction in its simplest form, 1/2 - 2/3 is equal to -1/6, or minus one-sixth.